Nivolumab-induced autoimmune diabetes mellitus presenting as diabetic ketoacidosis in a patient with metastatic lung cancer. Issue 1 (16th May 2017) - Godwin, James Luke; Jaggi, Shuchie; Sirisena, Imali; Sharda, Pankaj; Rao, Ajay D.; Mehra, Ranee; Veloski, Colleen
Abstract : Background: Advances in cancer immunotherapy have generated encouraging results in multiple malignancies refractory to standard chemotherapies. As the use of immune checkpoint inhibitors (ICI) proliferates, the incidence of autoimmune side effects associated with these agents, termed immune related adverse events (irAE), is expected to increase. The frequency of significant irAE in ICI treated patients is about 10–20% and early recognition is critical to prevent serious morbidity and even mortality. New onset autoimmune diabetes mellitus (DM) associated with immune checkpoint inhibitor treatment is extremely rare, occurring in less than 1% of patients. Autoimmune DM often presents as diabetic ketoacidosis, a medical emergency requiring immediate treatment. We describe the first reported case of a patient with lung cancer who developed autoimmune diabetes after nivolumab treatment and was found to have three diabetes related (islet) autoantibodies present before ICI treatment and seroconversion of another after ICI treatment and onset of autoimmune DM. Case Presentation: A 34 year old African American woman with metastatic non-small cell lung cancer (NSCLC) was treated with nivolumab in the second line setting after disease progression following standard chemoradiation therapy. After receiving two doses of nivolumab, the patient developed abrupt onset of hyperglycemia and diabetic ketoacidosis. Autoimmune diabetes was diagnosed on the basis of undetectable C-peptide levels, seropositivity of three diabetes related (islet) autoantibodies and absolute insulin dependence. The patient eventually required use of continuous subcutaneous insulin infusion (insulin pump) due to erratic glycemic excursions and multiple readmissions for DKA. Human leucocyte antigen (HLA) genoyping revealed none of the high risk haplotypes associated with the development of type 1 diabetes. Interestingly, a frozen blood sample obtained prior to treatment with nivolumab tested positive for three of the four diabetes related (islet) autoantibodies despite no prior history of diabetes and no family history of diabetes. Notably, at the time of manuscript preparation, the patient is without evidence of NSCLC recurrence with no further treatment since the nivolumab therapy. Conclusion: New onset autoimmune diabetes mellitus associated with nivolumab has been described only in case reports and occurs at rates of < 1% in the large clinical trials which garnered FDA approval in the second line setting for NSCLC. As ICI use continues to expand across a wide variety of malignancies, clinicians must maintain a high index of suspicion for irAE, including autoimmune DM and other endocrinopathies. A multidisciplinary team and thorough education of the patient are recommended to optimize management of new onset adult autoimmune DM. Our patient may have been at greater risk for the development of ICI related autoimmune diabetes due to the presence of three diabetes related autoantibodies prior to therapy; however, about half of the reported cases of autoimmune DM after anti-PD-1 therapy occurred in patients with no detectable diabetes related autoantibodies. Further studies are needed to delineate genetic and immunologic biomarkers that may be useful in identifying patients at risk of developing ICI related autoimmune DM.